Childhood abuse and cortical gray matter volume in patients with major depressive disorder. (January 2023) - Kim, Soo Young; An, Seong Joon; Han, Jong Hee; Kang, Youbin; Bae, Eun Bit; Tae, Woo-Suk; Ham, Byung-Joo; Han, Kyu-Man
Highlights: 75 patients with major depressive disorder (MDD) and 97 healthy controls. Childhood sexual abuse (CSA) was associated with gray matter volume reduction. CSA-associated volume reduction in the right middle occipital gyrus (MOG) was observed. MDD-associated volume reduction in the right anterior cingulate gyrus. More prominent volume reduction in patients with CSA compared to those without CSA. Abstract: Childhood abuse is associated with brain structural alterations; however, few studies have investigated the association between specific types of childhood abuse and cortical volume in patients with major depressive disorder (MDD). We aimed to investigate the association between specific types of childhood abuse and gray matter volumes in patients with MDD. Seventy-five participants with MDD and 97 healthy controls (HCs) aged 19–64 years were included. Cortical gray matter volumes were compared between MDD and HC groups, and also compared according to exposure to each type of specific childhood abuse. Emotional, sexual, and physical childhood abuse were assessed using the 28-item Childhood Trauma Questionnaire. Patients with MDD showed a significantly decreased gray matter volume in the right anterior cingulate gyrus (ACG). Childhood sexual abuse (CSA) was associated with significantly decreased gray matter volume in the right middle occipital gyrus (MOG). In the post-hoc comparison of volumes of the right ACG and MOG, MDD patients with CSA had significantly smaller volumes in the right MOG than did MDD patients without CSA or HCs. The right MOG volume decrease could be a neuroimaging marker associated with CSA and morphological changes in the brain may be involved in the pathophysiology of MDD.